Comparison between the Reflux Finding Score and the Reflux Symptom Index in the Practice of Otorhinolaryngology - Nunes, Heloisa Sobreira; Pinto, José Antonio; Zavanela, Adma Roberta; Cavallini, André Freitas; Freitas, Gabriel Santos; Garcia, Fabiola Esteves (International Archives of Otorhinolaryngology, 2016)
Introduction The Gastroesophageal Reflux Disease has a prevalence of ∼12% of the urban population in Brazil. Koufman proposed the term to designate Laryngeal Pharyngeal Reflux (LPR) symptoms, signs or tissue damage resulting from aggression of the gastrointestinal contents in the upper aerodigestive tract. Belafsky et al proposed a score that points to inflammatory laryngeal signs through videolaryngoscopic findings, the Reflux Finding Score (RFS). Moreover, in 2002, they published the Reflux Symptom Index (RSI).Objective The objective of this study is to provide a comparison between the Reflux Finding Score and the Reflux Symptom Index in the practice of Otorhinolaryngology.Methods Our study involved a total of 135 patients who visited the Ear, Nose, and Throat (ENT) clinic Núcleo de Otorrinolaringologia e Cirurgia de Cabeça e Pescoço de São Paulo between April 2014 and May 2015 with suspected LPR. We excluded nine patients and the study group was 126 patients. All patients were ranked by their RSI and RFS scores.Results The study group consisted of 126 patients (88 women and 38 men). Their main complaints were cough (40.4%), globus (21.4%), dysphonia (19.8%), throat clearing (15.8%), postnasal drip (3.17%), snoring (1.5%), dysphagia (1.5%), cacosmia (0.7%), and regurgitation (1.5%). The RSI ranges from 13 to 42 with a mean of 20.7 (SD = 6.67). The RFS ranged from 3 to 19 with a mean of 9.53 (SD = 2.64).Conclusion The RSI and RFS can easily be included in ENT routines as objective parameters, with low cost and high practicality. Based on the clinical index, the specialist can evaluate the need for further tests.
Keywords: gastroesophageal reflux disease; videolaryngoscopy; laryngopharyngeal reflux